Chronic Traumatic Encephalopathy: Is It Real? The Relationship Between Neurotrauma and Neurodegeneration. (August 2015) - Bailes, Julian E.; Turner, Ryan C.; Lucke-Wold, Brandon P.; Patel, Vimal; Lee, John M.
Abstract : Supplemental Digital Content is Available in the Text.